Effectiveness of Public Communication in Socializing Over Dimension Over Load (ODOL) Goverment Policy on Bogor Ciawi (BOCIMI) toll road - Suprayitno, Degdo; Susanti, Endang; Rachmat, Yusup; Latunreng, Wahyuddin (MSJ : Majority Science Journal, 2024)
Public comm  unication is the activity of understanding, designing, implementing, and evaluating communication campaigns in the public interest. Over Dimension Over Load (ODOL) is a logistics vehicle that transports goods excessively. The government is serious about curbing ODOL trucks, including revising vehicle weighing regulations. However, there are still problems in the implementation of the zero ODOL policy, such as ODOL practices that still often occur and vehicles with dimensions that do not comply with regulations.This research focuses on the effectiveness of public communication management in socializing the zero ODOL policy on the Bogor-Ciawi-Sukabumi (Bocimi) toll road. Using survey, observation, and questionnaire methods, this study explores how effective the socialization of this policy is on the toll road. The results show that the effectiveness of public communication in socializing the zero ODOL policy on the Bocimi toll road is quite effective, but still at the low limit. Factors that make socialization less effective include inadequate human resource conditions, low awareness and legal understanding of freight transportation entrepreneurs towards the zero ODOL policy.